The influencer industry : the quest for authenticity on social media - Hund, Emily (Princeton University Press, 2023)
"Before there were Instagram likes, Twitter hashtags, or TikTok trends, there were bloggers who seemed to have the passion and authenticity that traditional media lacked. The Influencer Industry tells the story of how early digital creators scrambling for work amid the Great Recession gave rise to the multibillion-dollar industry that has fundamentally reshaped culture, the flow of information, and the way we relate to ourselves and each other."--